The wheel of time eaudiobook The shamans of mexico their thoughts about life death and the universe. - Castaneda, Carlos (Recorded Books Inc., 2019)
World-renowned bestselling author Carlos Castaneda's Selection of his wrtings on the shamans of ancient Mexico. Originally drawn to Yaqui Indian spiritual leader don Juan Matus for his knowledge of mind-altering plants, bestselling author Carlos Castaneda soon immersed himself in the sorcerer's magical world entirely. Ten years after his first encounter with the shaman, Castaneda examines his field notes and comes to understand what don Juan knew all along-that these plants are merely a means to understanding the alternative realities that one cannot fully embrace on one's own. In Journey to Ixtlan, Carlos Castaneda introduces readers to this new approach for the first time and explores, as he comes to experience it himself, his own final voyage into the teachings of don Juan, sharing with us what it is like to truly "stop the world" and perceive reality on his own terms.